The Implementation of Confidence-Building Measures (CBMs) in the South China Sea for Regional Stability through the ASEAN Regional Forum (ARF) - Sembiring, Afri Emilia Br; Perwita, Anak Agung Banyu; Hadisancoko, Rizerius Eko; Wulandari, Adelia; Avanantsoa, Harlette Naudy Gea (The Republic of Indonesia Defense University, 2024)
Despite the ASEAN Regional Forum (ARF)’s efforts to implement confidence-building measures (CBMs) since its establishment in 1994, there are still challenges that remain in achieving the desired level of trust and cooperation among its 27 member countries, particularly in the South China Sea (SCS). While CBM initiatives have contributed to reducing tensions, there is still a gap further complicated by the shifting power dynamics, particularly China’s rise and the United States’ strategic responses, which have heightened tensions in the Indo-Pacific region. Furthermore, this study aims to assess the effectiveness of confidence-building measures (CBMs) in defense cooperation and diplomacy within the ASEAN Regional Forum (ARF), specifically in the context of the South China Sea (SCS). By analyzing the existing CBMs and identifying the gaps between the current state and the desired outcomes, the research seeks to provide insights into how these measures can be enhanced to manage tensions better, build trust, and promote regional stability amidst the evolving security landscape in the Indo-Pacific region. This research underscores the importance of CBMs in regional diplomacy and their potential to shape a stable and cooperative Indo-Pacific environment. The research used qualitative research methods, collecting data from scientific journals, websites, and previous research, which were analyzed to explore CBMs’ role in enhancing regional security and cooperation. Results indicate that CBMs have played a crucial role in promoting peace and stability in the Indo-Pacific and have been instrumental in reducing mistrust and preventing conflicts. However, challenges persist due to the complexity of regional security threats and the diverse interests of member states. Sustained cooperation and adaptability are essential to address evolving security dynamics. The effectiveness of CBMs in the SCS will depend on a commitment to dialogue among parties.